Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Global feminisms: new directions in contemporary art - Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center.; Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center. (Merrell ;, 2007)
Catalogue for the exhibition Global Feminisms, that took place at the Brooklyn Museum in 2007. The first international exhibition exclusively dedicated to feminist art from 1990 to the present. The show consists of work by approximately eighty women artists from around the world and includes work in all media—painting, sculpture, photography, film, video, installation, and performance. Its goal is not only to showcase a large sampling of contemporary feminist art from a global perspective but also to move beyond the specifically Western brand of feminism that has been perceived as the dominant voice of feminist and artistic practice since the early 1970s.This exhibition is arranged thematically and features the work of important emerging and mid-career artists.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Explorations in contemporary feminist literature: The battle against oppression for writers of color, lesbian and transgender communities - Pernal, Mary (Eruptions, 2002)
Explorations in Contemporary Feminist The Battle Against Oppression for Writers of Color, Lesbian and Transgender Communities is a work that bridges issues of oppression across diverse communities within the contemporary feminist movement. Fictional writings by authors such as Toni Morrison, Maya Angelou, Rose Tremain, and others are addressed in regard to their content of social messages. The major focus of this book is the need for personal-redefinition by members of marginalized communities seeking a ground of self-determination and respect, as expressed by various authors. The connections between authors' perspectives are rasied and a critical gaze is directed at the claim that personal choice equates with freedom.
Keywords: afro-féminisme; amériques; approches et analyses; arts; classisme; discipline; intersectionnalité; littérature; personnes lesbiennes; personnes trans*; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Post-colonial studies: The key concepts - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 2000)
This volume provides an essential key to understanding the issues which characterise post-colonialism, explaining what it is, where it is encountered and why it is crucial in forging new cultural identities. As a subject, post-colonial studies stands at the intersection of debates about race, colonialism, gender, politics and language. In the language of post-colonial studies, some words are new, others are familiar words charged with new significance.
Keywords: approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; intersectionnalité; littérature; premier cycle; ressource en ligne; thématiques; études culturelles; études littéraires